REGISTRATION AND FUSION OF MULTIPLE IMAGES ACQUIRED WITH MEDIUM FORMAT CAMERAS - Tommaselli, A. M. G. [UNESP]; Galo, M. [UNESP]; Marcato Junior, J. [UNESP]; Ruy, R. S.; Lopes, R. F. [UNESP]; ISPRS (Copernicus Gesellschaft Mbh, 2010)
Recent developments in the technology of optical digital sensors made available digital cameras with medium format at favourable cost/benefit ratio. Many companies are using professional medium format cameras for mapping and general photogrammetric tasks. Image acquisition systems based on multi-head arrangement of digital cameras are attractive alternatives enabling larger imaging area when compared to a single frame camera. Also, acquisition of multispectral imagery is facilitated with the integration of independent cameras. Several manufactures are following this tendency, integrating individual cameras to produce high-resolution multispectral images. The paper will address the details of the steps of the proposed approach for system calibration, image rectification, registration and fusion. Experiments with real data using images both from a terrestrial calibration field and an experimental flight, will be presented. In these experiments two Fuji FinePix S3Pro RGB cameras were used. The experiments have shown that the images can be accurately rectified and registered with the proposed approach with residuals smaller than 1 pixel.
Keywords: Photogrammetry; Dual Head; camera calibration; fusion of multiple images